2010
DOI: 10.1007/s10162-010-0232-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Signal Level and Background Noise on Spectral Representations in the Auditory Nerve of the Domestic Cat

Abstract: Background noise poses a significant obstacle for auditory perception, especially among individuals with hearing loss. To better understand the physiological basis of this perceptual impediment, the present study evaluated the effects of background noise on the auditory nerve representation of headrelated transfer functions (HRTFs). These complex spectral shapes describe the directional filtering effects of the head and torso. When a broadband sound passes through the outer ear en route to the tympanic membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
4
16
0
Order By: Relevance
“…Deviating from the physiological composition of the auditory nerve, where HSR fibers are the dominating population [13], we consider a composition of ANFs as 10 % for HSR, 20 % for MSR and 70 % for LSR fibers. This is consistent with the theory that neural coding may be disproportionately based on the enhanced dynamic range of LSR fibers in noisy environments as suggested in [14].…”
Section: Inner Ear Modelsupporting
confidence: 87%
“…Deviating from the physiological composition of the auditory nerve, where HSR fibers are the dominating population [13], we consider a composition of ANFs as 10 % for HSR, 20 % for MSR and 70 % for LSR fibers. This is consistent with the theory that neural coding may be disproportionately based on the enhanced dynamic range of LSR fibers in noisy environments as suggested in [14].…”
Section: Inner Ear Modelsupporting
confidence: 87%
“…This has been observed for vowels (Sachs and Young, 1979) and for DTF-filtered noise bursts (e.g. Reiss et al, 2011). Consistent with this, Alves-Pinto and Lopez-Poveda (2005) have reported that listeners’ ability to detect notches in wideband noise spectra declines with increasing stimulus intensity.…”
Section: Discussionmentioning
confidence: 54%
“…Reiss et al (2011) have, however, identified a population of low-spontaneous-rate (LSR), high-threshold fibers in the cat which have extremely large dynamic ranges, and for which spectral encoding remains robust at higher intensities. They propose that since cats’ vertical-plane localization performance does not decline at high intensities (for relatively long noise-burst stimuli), these fibers are the ones subserving vertical-plane localization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Judgments in the up/down and front/back dimensions are highly sensitive to signal-to-noise ratio (SNR) degradation (Good and Gilkey, 1996; Best et al, 2005). It has been suggested that the MOC system can help to counteract detrimental effects of background noise on sound localization by “un-masking” spectral cues (Reiss et al, 2011). Behavioral studies, which have found poorer sound-localization performance in cats with a lesioned OC system than in controls, have provided some support for this hypothesis (May et al, 2004).…”
Section: Introductionmentioning
confidence: 99%